CHEMICAL COMPOSITIONS AND AMINO ACIDS OF DOLPHIN FISH (Coryphaena hippurus) ROES - Johanna L. Thenu; Edir Lokollo; Max Robinson Wenno (Pattimura Proceeding, 2017)
Fish processing industry produces more than 60% of byproducts include the head, bones, fins, skin, viscera and roes. Only 40% of the total body of fish that can be consumed by humans. Byproduct of the fishing industry is a source of nutrition and functional food ingredients, such as roes have a high protein content and amino acids. The aim of this study was determine the chemical composition and amino acid profile of dolphin fish roe. The proximate composition of dolphin fish roe is protein 19.16%, fat 2.05%, moisture 72.94%, ash 1.12% and 4.72 carbohydrates. There are 17 amino acids in dolphin fish roe including proline (3.32%), arginine (3.01%), serine (2.85%) and phenilalanine (2.65 %) while the smallest amino acid is cystine (0.43%), histidine (1.22%) valine (1.34%) and methionine (1.36%).